(untitled) (London Journal of Medical and Health Research, 2025)
Background: The prevalence of obesity in students is currently increasing and it can lead to metabolic syndrome at such a young age. The habit of students who have bad sleeping pattern, night eating syndrome, and excessive SSB consumption can increase the risk of metabolic syndrome in obese students. Purpose: The purpose of this research was to analyze the differences of night eating syndrome, sleeping pattern, and consumption habit of sugar-sweetened beverage based on metabolic types in obese students. Method: The research was conducted in July-September 2020 with female students in Semarang City as subjects. This research used a case-control design, as many as 52 subjects aged 19-24 years were selected by consecutive sampling method. The collected data included: body weight using digital scales, height using a microtoise, waist size using a medline, blood pressure using a tensimeter, and a laboratory tests was conducted to check triglyceride levels, HDL cholesterol, fasting blood glucose, as well as insulin. The used instruments were The Night Eating Questioner (NEQ) to assess the night eating syndrome, Pittsburg Sleep Quality (PSQI) to assess sleeping pattern, and Semi-Quantitative Food Frequency Questionnaire (SQFFQ) to see the subject’s consumption of sugar-sweetened beverage during the last one month. The data were analyzed using Chi-Square test. Result: The research showed that majority of the subjects who experienced night eating syndrome (46,2%) and bad sleeping pattern (61,5%) were subjects with Metabolically Unhealthy Obesity (MUO). Meanwhile, for sugar-sweetened beverage consumption in Metabolically Healthy Obesity (MHO) and Metabolically Unhealthy Obesity (MUO) were still within the normal range (86,4%). A difference between night eating syndrome (p=0,006) and sleeping pattern (p=0,012) on Metabolically Healthy Obesity (MHO) and Metabolically Unhealthy Obesity (MUO) was also observed. Conclusion: Students with Metabolically Unhealthy Obesity (MUO) type were experiencing more night eating syndrome and bad sleeping pattern compared to the students with Metabolically Healthy Obesity (MHO) type.